Analysis of Employee Commitment to the Organization with Job Involvement as an Intervening Variable at PT. X - Sunaryo, Alda Clarissa; Yulivan, Ivan; Nawir, Jubaedah (Ilomata International Journal of Management, 2024)
The development of information technology has transformed business and daily life. Organizational transformations are precipitated by the advancement of information technology. In the 21st century, loyal, committed, and dedicated employees are a company's most valuable asset since they perform better and spend more time improving organizational outcomes. This study aims to analyze the effect of work motivation, job security, and organizational climate on employee commitment to the organization, with job involvement as an intervening variable at PT. X. This research used a non-experimental quantitative research method with a total sampling technique, collecting data from 117 respondents using valid and reliable questionnaires. The research results were analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM) with Smart PLS version 3. The findings demonstrate that employee commitment to the organization is positively and significantly affected by work motivation, job security, and organizational climate. Furthermore, through job involvement as an intervening variable, work motivation, job security, and organizational climate exert a positive and significant indirect effect on employee commitment. However, their direct effects on employee commitment to the organization are greater than the indirect effects mediated by job involvement.